The Relationship of Supervision with Nurses' Hand Hygiene Compliance - Minnatun Khasha; Meri Anggryni; Yersi Ahzani; Ni Luh Seri Astuti (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the places with high occupational risks and threatening the safety and health of human resources within it is a hospital, which is not only a place of treatment but can be a source of infection for patients, visitors, and staff. Hand hygiene is one of the efforts that can be made to prevent diseases, especially those transmitted through the hands. Hand hygiene is carried out to remove dirt or kill microorganisms on the skin by washing hands in 6 steps and 5 moments. The research was conducted to determine the relationship between supervision and hand hygiene compliance by nurses in the inpatient room at KH Daud Arif Kuala Tungkal Hospital. This research is a quantitative study with a cross-sectional design. Results: The research shows a significant relationship between supervision and compliance of implementing nurses in carrying out hand hygiene in the inpatient room at KH Daud Arif Kuala Tungkal Regional Hospital with a p-value of 0.024. It is hoped that the hospital will continue to consistently carry out supervision to increase the compliance of implementing nurses in carrying out hand hygiene.